Surface Functionalization of g‐C3N4: Molecular‐Level Design of Noble‐Metal‐Free Hydrogen Evolution Photocatalysts. Issue 29 (12th June 2015) - Chen, Yin; Lin, Bin; Yu, Weili; Yang, Yong; Bashir, Shahid M.; Wang, Hong; Takanabe, Kazuhiro; Idriss, Hicham; Basset, Jean‐Marie
Abstract A stable noble‐metal‐free hydrogen evolution photocatalyst based on graphite carbon nitride (g‐C3N4) was developed by a molecular‐level design strategy. Surface functionalization was successfully conducted to introduce a single nickel active site onto the surface of the semiconducting g‐C3N4. This catalyst family (with less than 0.1 wt % of Ni) has been found to produce hydrogen with a rate near to the value obtained by using 3 wt % platinum as co‐catalyst. This new catalyst also exhibits very good stability under hydrogen evolution conditions, without any evidence of deactivation after 24 h.